Epidermal growth factor receptor and KRAS mutations in Brazilian lung cancer patients (Clinics, 2012)
OBJECTIVE: Epidermal growth factor receptor is involved in the pathogenesis of non-small cell lung cancer and has recently emerged as an important target for molecular therapeutics. The KRAS oncogene also plays an important role in the development of lung cancer. The aim of this study was to evaluate the frequency of epidermal growth factor receptor and KRAS mutations in a population of Brazilian patients with non-small cell lung cancer. METHODS: A total of 207 specimens from Brazilian patients with non-small cell lung cancer were analyzed for activating epidermal growth factor receptor and KRAS somatic mutations, and their associations with clinicopathological characteristics (including age, gender, ethnicity, smoking habits, and histological subtype) were examined. RESULTS: We identified 63 cases (30.4%) with epidermal growth factor receptor mutations and 30 cases (14.6%) with KRAS mutations. The most frequent epidermal growth factor receptor mutation we detected was a deletion in exon 19 (60.3%, 38 patients), followed by an L858R amino acid substitution in exon 21 (27%, 17 patients). The most common types of KRAS mutations were found in codon 12. There were no significant differences in epidermal growth factor receptor or KRAS mutations by gender or primary versus metastatic lung cancer. There was a higher prevalence of KRAS mutations in the non-Asian patients. Epidermal growth factor receptor mutations were more prevalent in adenocarcinomas than in non-adenocarcinoma histological types. Being a non-smoker was significantly associated with the prevalence of epidermal growth factor receptor mutations, but the prevalence of KRAS mutations was significantly associated with smoking. CONCLUSIONS: This study is the first to examine the prevalence of epidermal growth factor receptor and KRAS mutations in a Brazilian population sample with non-small cell lung cancer.